(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This text explores the nature and mechanisms of fraud involving debit, credit, and virtual cards. It provides a detailed overview of the specific vulnerabilities associated with each card type, the evolving techniques used by fraudsters—such as phishing, skimming, data breaches, and social engineering—and the various digital and behavioral strategies to prevent unauthorized access. Emphasis is placed on both technological safeguards, like tokenization and biometric authentication, and individual responsibility, such as cautious online behavior and vigilant account monitoring. The text underlines that combating card fraud requires a multi-layered approach involving users, financial institutions, and regulatory bodies working in tandem.